THE FUNCTIONAL RELATIONSHIP BETWEEN BADAN NARKOTIKA NASIONAL (NATIONAL NARCOTICS AGENCY) AND CORRECTIONAL INSTITUTIONS IN DEALING WITH THE ISSUE OF NARCOTICS AT CORRECTIONAL INSTITUTIONS - Muhammad Amin Imran (Jurnal IUS Kajian Hukum dan Keadilan, 2013)
Therefore, there should be an effort to prevent and to fight against the drug abuse and illicit trafficking in Penitentiary. But, in handling narcotic in Penitentiary there is conflict of authority between National Narcotic Agency (BNN) which is in charge to carry out the drug abuse and narcotic circulation and the authority in the Penitentiary . BNN which is incharge to make and to implement the policies of  preventing, fighting against the drug abuse and narcotic circulation works based on : the Law No. 35 of 2009 concerning on the Narcotic, although prior to that, there are such laws as Instructions of President No. 6 of 1971, Presidential Decree No. 116 of 1999 about National Drug Coordination Body, Presidential Decree No. 17 of 2002 on the National Narcotic Agency (BNN), Presidential Regulation No. 83 of 2007 on the National Narcotic Agency (BNN),  Provincial Narcotic Agency and District Narcotic Agency, and Presidential Regulation No. 23 of 2010 on National Narcotic Agency (BNN). Then,  the implementation of the functional relation between National Narcotic Agency and Penitentiary in handling narcotic in penitentiary has not been going well due to the  duty-related conflict of authority and that should be  synchronized by applying the principle of Lex Specialist Derogat Legi Generalist. Thus, it is necessary to make a good functional pattern of relation between National Narcotic Agency and Penitentiary in handling the narcotic in Penitentiary in the future. The pattern should be a coordinated relation that is preventive and repressive based on the MoU between National Narcotic Agency and Penitentiary.Keywords : Functional Relation, National Narcotic Agency (BNN) and Penitentiary (Lapas)